OVARIAN RESERVE IN THE WOMEN OF LATE REPRODUCTIVE AGE AFTER CONSERVATIVE TREATMENT OF POLYCYSTIC OVARIAN SYNDROME (PCOS) IN ADOLESCENCE - K. G. Beltadze; L. Barbakadze; A. G. Khomasuridze (Акушерство, гинекология и репродукция, 2016)
Background: the aim of the present study was to assess of the ovarian reserve of the women of late reproductive age after the conservative treatment of polycystic ovarian syndrome in adolescence. Design: the study was a longitudinal retrospective by purposive sampling. Methods: a total of 67 women of late reproductive age with confirmed primary PCOS in adolescence and 70 healthy age-matched controls were included in the study. The patients with PCOS underwent clinical investigation and conservative treatment with antiandrogens and oral contraceptive pills (OCPs) between 1984 and 1990y. and at the time of original diagnosis they were 13-18 y. Main outcome measures: the patients were collected via analysis of histories at primary diagnosis of PCOS in adolescence and at the time of the follow-up investigation of reproductive hormones was conducted. Data were compared between the study and control groups. Results: after conservative treatment PCOS patients had higher levels of anti-Müllerian hormone and greater number of antral follicles than controls (p <0.01 and p <0.05 respectively). Conclusions: our data suggest that PCOS patients who underwent conservative treatment in adolescence have the better ovarian reserve in late reproductive age than control women.